Longitudinal changes in functional connectivity in speech motor networks in apraxia of speech after stroke - Hybbinette, Helena; Östberg, Per; Schalling, Ellika; Deboussard, Catharina; Plantin, Jeanette; Borg, Jörgen; Lindberg, Påvel G. (Frontiers in Neurology, 2022)
Objective: The cerebral substrates of apraxia of speech (AOS) recovery remain unclear. Resting state fMRI post stroke can inform on altered functional connectivity (FC) within cortical language networks. Some initial studies report reduced FC between bilateral premotor cortices in patients with AOS, with lowest FC in patients with the most severe AOS. However, longitudinal FC studies in stroke are lacking. The aims of the present longitudinal study in early post stroke patients with AOS were (i) to compare connectivity strength in AOS patients to that in left hemisphere (LH) lesioned stroke patients without a speech-language impairment, (ii) to investigate the relation between FC and severity of AOS, aphasia and non-verbal oral apraxia (NVOA) and (iii) to investigate longitudinal changes in FC, from the subacute phase to the chronic phase to identify predictors of AOS recovery. Methods: Functional connectivity measures and comprehensive speech-language assessments were obtained at four weeks and six months after stroke in nine patients with AOS after a LH stroke and in six LH lesioned stroke patients without speech-language impairment. Functional connectivity was investigated in a network for speech production: inferior frontal gyrus (IFG), anterior insula (aINS), and ventral premotor cortex (vPMC), all bilaterally to investigate signs of adaptive or maladaptive changes in both hemispheres. Results: Interhemispheric vPMC connectivity was significantly reduced in patients with AOS compared to LH lesioned patients without speech-language impairment. At six months, the AOS severity was associated with interhemispheric aINS and vPMC connectivity. Longitudinal changes in FC were found in individuals, whereas no significant longitudinal change in FC was found at the group level. Degree of longitudinal AOS recovery was strongly associated with interhemispheric IFG connectivity strength at four weeks. Conclusion: Early interhemispheric IFG connectivity may be a strong predictor of AOS recovery. The results support the importance of interhemispheric vPMC connection in speech motor planning and severity of AOS and suggest that also bilateral aINS connectivity may have an impact on AOS severity. These findings need to be validated in larger cohorts.